The Need for a New, Clear Option: An In-Depth Analysis of Nuclear Energy - Davis, Zachary Evan (Consilience, 2015)
The goal of the research presented here will be to provide a comprehensive view of the nuclear industry today. Upon analyzing data from the last 40 years, a pattern of irresponsible, financially untenable policymaking begins to emerge, highlighting the growing disconnect between the general populace, which is most vulnerable to the benefits and pitfalls of the nuclear industry, and the elected officials who make the final decision in many countries regarding nuclear adoption. The primary context of this article will be concerned with analyzing opposing views of how nuclear power normally stands to benefit mankind versus the impacts of a worst case nuclear disaster, as occurred at the Fukushima Daiichi Nuclear Plant. The author provides a brief, general overview of the theory behind nuclear power and its impacts before moving on to the benefits and drawbacks faced by adoptive communities. Next, an analysis of the financial viability of the nuclear industry will be offered, as well as a brief introduction of several means of generating electricity, and their general benefits and drawbacks. The author then offers an opinion on which of these options would offer the best alternative to nuclear power in both the short and long term. Finally, government patterns of dealing with nuclear power will be examined; it very quickly becomes evident that even in the most transparent societies, nuclear adoption encourages dishonesty from policy makers. In closing, the author will leave the reader with a troubling question: “Do we really have a say in our own future?”